Knowledge and attitude of rural population towards TB and perception of barriers in accessing to TB services in two provinces of Afghanistan - Islam, Qazi Shafayetul; Ahmed, Syed Masud; Rahman, Taufiqur; Amin, Sher Shah; Rahman, Mashuqur (BRAC Research and Evaluation Division (RED), 2019)
The study aimed to explore i) the awareness and knowledge on tuberculosis (TB), ii) knowledge on TB diagnosis and treatment, iii) attitudes towards TB, and iv) perception of barriers in accessing to TB services. The approach adopted for this study was cross-sectional, multi-stage 30-cluster sampling method, face to face interview with adult male and female (aged + 15 year) in Badghis and Balkh provinces of Afghanistan. The total sample size was 900. The general awareness about ·rs was high in both the provinces (around 96%). TB was perceived widely as dangerous (81 %), and incurable (85%) by the population in both the provinces. A misperception that 'TB is a disease of female' was also observed in these provinces (78%) . Though the knowledge on symptom suggestive of TB (chronic cough) was high (9 I%), they lacked knowledge on other associated symptoms of TB. Knowledge on microbiological cause of TB was totally absent. However, they had different cultural explanations for the causation of TB. The knowledge on transmission and prevention was not comprehensive and varied by province and gender. Knowledge on diagnostic test was high (S5%), but when to test sputum was poor (26%). Knowledge on place of diagnosis was lacking. Respondents had also poor knowledge on management of TB (e.g., treatment duration, place of treatment). Tendency to seek care from government facilities lnr TB treatment was low ( 18%) in Afghanistan despite TB services offered free at government health facilities. Population had less access to community health workers (CHW) and public facilities for obtaining TB information. TB patients in both the provinces prioritized work over taking TB treatment. Besides, financial problem, shame and fear of isolation were found to be important deterrents in accessing to TB care. Health education content and materials should be reviewed and redesigned appropriately tnr disseminating comprehensive information on TB causation, transmission, prevention, diagnostic place and misperception associated with TB as well. A social support network (SSN) should be established within the community to support the TB patients to overcome the barriers.